2017
DOI: 10.1097/md.0000000000007524
|View full text |Cite
|
Sign up to set email alerts
|

The effect of care intervention for obese patients with type II diabetes

Abstract: The incidence of type II diabetes mellitus (T2DM) is increasing worldwide and affecting the quality of people's life. This study was designed to evaluate the effect of care intervention on body weight and glycemic parameters in obese T2DM patients.One hundred twenty-six obese T2DM cases were randomly divided into 2 groups. Patients in control group received conventional care, while patients in the intervention group received dietary, exercise, and psychology interventions on the basis of conventional care. Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 32 publications
3
5
0
Order By: Relevance
“…These changes in dietary habits resulted in changes in the clinical variables. These changes correspond to those achieved by other multifactorial interventions such as that of Jiang et al [39], who observed a decrease in postprandial glycaemia (10.7 ± 3.2 vs. 5.8 ± 2.1 mmol/L) in the IG after 12 months of follow-up, through changes in diet, exercise and a psychological approach. In the same way, several studies [39,40,41,42] have managed to significantly improve BMI among other parameters through a multifactorial intervention based on changes in diet and exercise in subjects with T2DM.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These changes in dietary habits resulted in changes in the clinical variables. These changes correspond to those achieved by other multifactorial interventions such as that of Jiang et al [39], who observed a decrease in postprandial glycaemia (10.7 ± 3.2 vs. 5.8 ± 2.1 mmol/L) in the IG after 12 months of follow-up, through changes in diet, exercise and a psychological approach. In the same way, several studies [39,40,41,42] have managed to significantly improve BMI among other parameters through a multifactorial intervention based on changes in diet and exercise in subjects with T2DM.…”
Section: Discussionsupporting
confidence: 86%
“…These changes correspond to those achieved by other multifactorial interventions such as that of Jiang et al [39], who observed a decrease in postprandial glycaemia (10.7 ± 3.2 vs. 5.8 ± 2.1 mmol/L) in the IG after 12 months of follow-up, through changes in diet, exercise and a psychological approach. In the same way, several studies [39,40,41,42] have managed to significantly improve BMI among other parameters through a multifactorial intervention based on changes in diet and exercise in subjects with T2DM. Finally, we think that the results obtained in this work could be pioneering, since as far as we know, this study is the first to analyse the effects of a multifactorial intervention on diet in subjects with T2DM based on a food workshop and a smartphone application, as well as achieving improvement in the MEDAS and the DQI questionnaire.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, the results are consistent with Pourgholami et al (2017), Nadine Kuniss et al (2018), and Jiang et al (2018)[18][19][20]. The findings can be considered as indicators of effectiveness of the educational strategy.…”
supporting
confidence: 89%
“…Recent studies show the benefits of different types of physical exercise and highlight LGI foods as part of the nutritional intervention in individuals with type 2 DM. 24,25 In contrast, in recent studies of exercise and DM type 1, pre-exercise food GI is not clearly considered as a nutritional care option for glycemic control during physical exercise. 26,27 This current view may reflect that the relevance of GI to clinical practice is not yet clear.…”
Section: Discussionmentioning
confidence: 99%